Syndrome Of The Metro Urban Streamflow In Malang City, Indonesia - Azwar Ali; Mangku Purnomo; Soemarno Soemarno (Indonesian Journal of Environment and Sustainable Development, 2012)
Purpose of this research was to describe the quality of streamflow water and community behavior around the streamflow in utilizing water. It is found that  an increasing number of residents in the Malang city along the Metro strteamflow have resulted in a decline of water quality, it is related to the behavior of the community in utilizing streamflow for their daily needs. These behavior is strongly affected by the knowledge, socioeconomic conditions, and access of informations about streamflow ecosystem and water quality. The community along the Metro streamflow in Malang city suggest a very strong dependence on this streamflow for their daily needs. Changes in streamflow ecosystems and its water quality are perceived very deeply by the surrounding people. Water quality problems are the strategic issues to be solved by the local government, together with the urban communities and other stekeholders. Keywords: human behavior, streamwater quality.